New developments in maize - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
The highly protein-rich varieties of maize are gaining a new footing in the developing countries of Latin America, the Caribbean Islands, West Africa and Asia. In fact, the research conducted by the International Maize and Wheat Improvement Centre...